Exploring the metadiscursive realisation of incivility in TV news discourse. (March 2020) - McKeown, Jamie; Ladegaard, Hans J.
Highlights: We explore the metadiscursive realisation of incivility in TV news discourse. (In)civlity is treated as separate from (Im)politeness. Five salient aspects of incivility are presented. Metadiscourse is shown as central to the realization these aspects of incivility. Abstract: The present paper examines the use of metadiscourse in the realisation of incivility in TV news discourse. We take empirical data from a UK Channel 4 News interview between TV journalist and author Cathy Newman and clinical psychologist and author Professor Jordan Peterson. Adopting a discourse analytic approach, five aspects of incivility are presented: intolerant response; ideological entrenchment; low oppositional literacy; the need to win; and, change of opinion condemnation. We show how metadiscourse is used to manifest incivility in a number of ways including to prioritise the current speaker's foci over those of the interlocutor; to express metalingual commentary which negatively characterises the interlocutor's discourse; and, to express discourse norms which undermine the open exchange of ideas. We conclude by suggesting recommendations for future research.